The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2621.2004.tb10997.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Proteins and Polysaccharides on Physical Properties of Whey Protein Concentrate‐based Edible Films

Abstract: The water-vapor permeability (WVP) and mechanical properties of edible films formed from dry blends or co-dried preparations of protein-polysaccharide powders prepared from whey protein concentrate ( WPC)-45 and alginate, pectin, carrageenan, or konjac flour ( WPC-45-to-polysaccharide ratio of 95:5 w/w) were investigated. Films were prepared from 8% WPC using WPC-45 (45% protein powder), consisting of 17.76 g of WPC-45 in 82.84 g of water per 100 g solution to give 8% protein w/w. Films formed from co-dried po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
3
51
0
Order By: Relevance
“…After studying the effect of adding other polysaccharides and proteins, such as cellulose, hemicellulose and corn zeins to the formulation, Gáspár et al (2005) concluded that hemicellulose and zeins conferred the best mechanical properties to the resulting materials. Other authors also reported that combining starches with other biopolymers, such as proteins or cellulose, results in the formation of biodegradable materials with improved properties (Arvanitoyannis, Psomiadou, & Nakayama, 1996;Arvanitoyannis, Psomiadou, Nakayama, Aiba, & Yamamoto, 1997;Coughlan, Shaw, Kerry, & Kerry, 2004;Jagannath, Nanjappa, Das Gupta, & Bawa, 2003;Psomiadou, Arvanitoyannis, & Yamamoto, 1996;Wongsasulak et al, 2006;Wongsasulak, Yoovidhya, Bhumiratana, & Hongsprabhas, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…After studying the effect of adding other polysaccharides and proteins, such as cellulose, hemicellulose and corn zeins to the formulation, Gáspár et al (2005) concluded that hemicellulose and zeins conferred the best mechanical properties to the resulting materials. Other authors also reported that combining starches with other biopolymers, such as proteins or cellulose, results in the formation of biodegradable materials with improved properties (Arvanitoyannis, Psomiadou, & Nakayama, 1996;Arvanitoyannis, Psomiadou, Nakayama, Aiba, & Yamamoto, 1997;Coughlan, Shaw, Kerry, & Kerry, 2004;Jagannath, Nanjappa, Das Gupta, & Bawa, 2003;Psomiadou, Arvanitoyannis, & Yamamoto, 1996;Wongsasulak et al, 2006;Wongsasulak, Yoovidhya, Bhumiratana, & Hongsprabhas, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…While the need for more studies on the rheology of WPI has been emphasised (Coughlan et al, 2004), many studies on whey-starch mixtures, including those referred to above, concentrated on cooled gels, and information on changes to starch gelatinisation and retrogradation during cooking and cooling of whey-starch systems is limited. Goel et al used the Brabender amylograph to study viscosity development in starch-casein systems at 5% solids.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of a low concentration of ALG, the influence of ALG on the interactions of the co-blending system was comparatively lower; as a result, interaction between SPI and ALG did not occur. In contrast, for SPI:ALG ¼ 10:1 or SPI:ALG ¼ 20:1, with the addition of ALG within a suitable concentration range with co-drying, the intermolecular force between different SPI/ALG components was effective, and the interfacial tension between different phases decreased and adhesion degree and compatibility degree increased; as a result, the Tg value of the co-blending system was significantly increased (Coughlan, Shaw, Kerry, & Kerry, 2004;Salvador, Sanz, & Fiszman, 2001;Turgeon & Beaulieu, 2001).…”
Section: Tg Of Phase-separated Co-blending Systemsmentioning
confidence: 68%